The Effect of Tunneling Incentives and Tax Burden on Transfer Pricing in Companies Listed in the Jakarta Islamic Index 70 for the Period 2020–2023 - Elsafira Putri; Ilham Illahi; Zuwardi Zuwardi; Amsah Hendri Doni (Yayasan Rahmat Islamiyah, 2026)
This study highlights the effect of tunneling incentives and tax burden on transfer pricing. A quantitative method was employed, using secondary data obtained from the official website of the Indonesia Stock Exchange (IDX) (www.idx.co.id), with a sample of 61 companies. The results indicate that tunneling incentives have a positive effect on transfer pricing in companies listed on the Jakarta Islamic Index 70 during the 2020–2023 period; therefore, H1 is accepted. The tax burden has a negative effect on transfer pricing in companies listed on the Jakarta Islamic Index 70 during the 2020–2023 period; therefore, H2 is rejected. Tunneling incentives and tax burden simultaneously and significantly affect transfer pricing in companies listed on the Jakarta Islamic Index 70 during the 2020–2023 period; therefore, H3 is accepted.